2005
DOI: 10.1590/s0100-879x2005000500008
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary bypass alters the pharmacokinetics of propranolol in patients undergoing cardiac surgery

Abstract: The pharmacokinetics of propranolol may be altered by hypothermic cardiopulmonary bypass (CPB), resulting in unpredictable postoperative hemodynamic responses to usual doses. The objective of the present study was to investigate the pharmacokinetics of propranolol in patients undergoing coronary artery bypass grafting (CABG) by CPB under moderate hypothermia. We evaluated 11 patients, 4 women and 7 men (mean age 57 ± 8 years, mean weight 75.4 ± 11.9 kg and mean body surface area 1.83 ± 0.19 m 2 ), receiving pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
5

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 30 publications
(32 reference statements)
0
12
0
5
Order By: Relevance
“…This risk score takes into account the following variables: a) emergency procedure, b) preoperative serum creatinine levels, c) presence of left ventricular dysfunction, d) preoperative hematocrit, e) age, f) chronic pulmonary disease, g) prior vascular surgery, h) reoperation, and i) mitral valve insufficiency. Partial results concerning patients receiving propranolol have been already reported elsewhere (10). Body surface area (BSA) and lean body mass (LBM) were calculated using standard formulas, as follows: BSA (m²) = ([height (cm) x weight (kg)] / 3600) ½ ; LBM men (kg) = (1.10 x weight (kg)) -128 (weight 2 / (100 x height (m)) 2 ) and LBM women (kg) = (1.07 x weight (kg)) -148 (weight 2 / (100 x height (m)) 2 ).…”
Section: Methodsmentioning
confidence: 86%
See 1 more Smart Citation
“…This risk score takes into account the following variables: a) emergency procedure, b) preoperative serum creatinine levels, c) presence of left ventricular dysfunction, d) preoperative hematocrit, e) age, f) chronic pulmonary disease, g) prior vascular surgery, h) reoperation, and i) mitral valve insufficiency. Partial results concerning patients receiving propranolol have been already reported elsewhere (10). Body surface area (BSA) and lean body mass (LBM) were calculated using standard formulas, as follows: BSA (m²) = ([height (cm) x weight (kg)] / 3600) ½ ; LBM men (kg) = (1.10 x weight (kg)) -128 (weight 2 / (100 x height (m)) 2 ) and LBM women (kg) = (1.07 x weight (kg)) -148 (weight 2 / (100 x height (m)) 2 ).…”
Section: Methodsmentioning
confidence: 86%
“…Because it is known that the dose of propranolol necessary to obtain an adequate β-blockade effect in the postoperative period, in order to reduce heart rate to <100 beats per minute (bpm), is lower than the preoperative dose, we carried out a clinical study (10) that showed that cardiopulmonary bypass (CPB) alters the kinetic disposition of propranolol in patients undergoing cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%
“…However, the recommended period for discontinuation of the drug prior to the surgery is still controversial. Barazzone and co-workers (1988) proposed an interval of 6 to 8 h after the last propranolol dose, whereas other investigators recommend a longer period ranging from 12-18 h up to 24 h (maximum) before the beginning of the surgical procedure 6,17 . For interpretation of the results (Table 5), plasma propranolol concentrations were normalized to measure the effect of hemodilution caused by the CPB during the surgery.…”
Section: Quantification Of Propranolol In Plasma Of Patients Submittementioning
confidence: 99%
“…On the other hand, when CPB is installed and hemodilution occurs, the plasma propranolol concentration decreases by 50%. In addition, fatsoluble drugs such as propranolol are easily sequestered by the circulator, a fact that contributes to a reduction of plasma propranolol levels during CPB 6 . In the present study, surgery was started about 15h after administration of the last preoperative propranolol dose.…”
Section: Quantification Of Propranolol In Plasma Of Patients Submittementioning
confidence: 99%
See 1 more Smart Citation